Coloniality of power and social control strategies in mining: an analysis of MAM activists' narratives. - Lima, Andreina Del Carmen Camero de; Mafra, Flávia Luciana Naves (Third World Quarterly, 2023)
Brazil has experienced the expansion of mining in recent years, guided mainly by the neoextractive model. This exploitation model has been imposed by a hegemonic discourse that considers mining as a need for the development of periphery countries. But cases such as the failure of the dams in Mariana and Brumadinho confirm that this model has brought more negative impacts than benefits and development for the local communities. In this context, many resistance movements have emerged to confront mineral exploitation. At the same time, mining companies have adopted strategies to protect their interests. The study objective is to analyse the strategies of social control adopted by corporations to guarantee their domination in mining territories, based on the narratives of activists from the Movement for Popular Sovereignty in Mining (MAM), interpreted from the perspective of coloniality of power. Results reveal that mining companies are central agents in neoextractivism, reproducing the coloniality of power through social control strategies, reinforcing subalternisation of vulnerable populations and making it more difficult for communities to resist mining.